TARI BARONGAN KUCINGAN PADA PERTUNJUKAN JARANAN KELOMPOK SENI GUYUBING BUDAYA DI KOTA BLITAR - Sisilia Dian Santika Dewi (Institut Seni Indonesia Surakarta, 2015)
The Barongan Kucingan dance is a dance which imitates the movements of a cat and issupported by properties in the form of a barongan(a lion’s head) that covers the face of the dancer.The Barongan Kucing dance is believed to depict the King Singo Barong. This research aims tofind out more about the form and role of the Barongan Kucing dance as performed by the GuyubingBudaya Art Group at a Jaranan art performance in the town of Blitar. The research is qualitativein nature and uses an analytical descriptive method which analyzes the results of the observationin the field and describes them in written form. One of the stages of the research is data collection,obtained through a library study, observation, documentation, and interviews. The results of theresearch about the form of the Barongan Kucing danceas performed by the Guyubing Budaya ArtGroup show in detail various aspects or elements of its choreography, including the dancer, themovements, the floor patterns, the music, the costumes, and the properties. The role of the BaronganKucing dance in the Jaranan art performance by the Guyubing Budaya Art Group is to attract theattention of the audience at the start of the performance and again at the end of the performance toprovide a climax which is marked by a trance dance.Keywords: Form of Performance, Barongan Kucingan Dance, and Role.